ANALISIS PEMILIHAN MODA ANTARA KERETA API PRIANGAN EKSPRESS DENGAN BUS JURUSAN BANJAR - JAKARTA (Studi Kasus Rencana Pengoperasian KA. Priangan Ekspress Rute : Banjar - Jakarta) - , DANI HARDIANTO ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Public transport service available to serve community in Banjar, Ciamis and Tasikmalaya who would travel to the area of Bandung or Jakarta was only Bus. Thus, on August 12, 2009 PT. KAI officially operated Train âPriangan Ekspress" services from Banjar to Pasar Senen Jakarta. After 3 months of operation, Priangan Express train stopped operating because the occupancy rate was only 30 percent. Currently, there is a discourse about reopening Train Priangan express. This research focuses on the study of characteristics and analyzes the level of train Priangan Express demand. It is done by identifying factors which influence the mode choice of Priangan Express. Difference analysis between Train Priangan Express and regular bus is done by using stated preferences method. Thus, the mode choice model is found (split capital model) between the two modes of transport. The probability of mode choice between train Priangan Express and Regular Bus is measured with the binomial logit function. The result shows that most influential factors are travel expenses, travel time and travel convenience. Based on the mode choice model application with 8 scenarios, if Train Priangan Express system is implemented then at scenario 1,2,3,4,5 and 6 Bus passengers "definitely choose" and "maybe chooseâ Bus. While in scenario 7 and 8, if Train Priangan Express system is applied according to the scenario, Bus passengers "maybe choose" Train with opportunities ranging from 54% - 58%. PT. KAI only need 24,38% demand of all market shares to meet the quota of train Priangan Express. Based on this, then by applying the attribute value in the scenario 8 (ÎTravel Time -90 and Îcomfort 0), with Îtariff as much as Rp . 34 500,- PT. KAI has been able to meet quota. At the same condition, if the PT. KAI applies attribute value in the scenario 8 (ÎTariff 20.000 and Îcomfort 0), PT. KAI has been able to meet the required quota with the provision Ît_travel is changed to only -65 minutes.